The Inner Form of the Word in the Mirror of Language Play - Сніховська, Ірена Едуардівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is devoted to highlighting the meaning of the inner form of the word for studying the phenomenon of language play. It is emphasized that the inner form acts as an associative core of sign perception, therefore, to create ludic units in the situations of language play, the linguo-creative personality uses the potential of the inner and outer structures of the word. The paper seeks to address the issue of creating the ludic units in the associative field of language play as the process in which the participants of the communicative interaction employ the lingual associative code, based on analogies between signs, phonetic deformations of the outer form of the words, combining language features of phonological, word-building, syntactic levels, and is based on either sound and structural analogy or phonetic deformation, the use of an unconventional grammatical form, etc. The conclusion is drawn that the study of the inner form of the word in the mirror of the language play opens up the possibilities of (re)constructing the associative valency of the language sign, the links of the language nomination, making possible an impact on the intellectual and emotional sphere of the addressee.